Gogolj, Melville in Fran Erjavec - Kos, Janko (Slavistična revija, 2006)
The focusses on the comparison of the narrative about the image and fate of a scribe, created in the 19th century: Gogol's The Overcoat, Melvill's Barteleby, and Erjavec's Avguštin Ocepek. Its goal is to analyze and explain the differences in the formulation of the same motif in Russian, American, and Slovene literature, i.e., in terms of form as well as content. It explains them with socio-cultural, and intellectual-historical backgrounds, from which the narratives by the three authhors are derived.
Keywords: 19. str.; 19th century; American literature; ameriška književnost; Erjavec, Fran, 1834-1887; Gogol', Nikolaj Vasil'evič, 1809-1852; humoreska; humoresque; kratka proza; Melville, Herman, 1819-1891; novela; novella; ruska književnost; Russian literature; short story; Slovene literature; slovenska književnost; značajevka